Analisis Strategi Guru dalam Meningkatkan Motivasi Belajar Peserta Didik SMP Negeri 2 Gunungsitoli - Moriani Tafonao; Novelina Andriani Zega; Hardikupatu Gulo; Desman Telaumbanua (Departement of Mathematics Education, 2024)
This research is motivated by the attitude of students who are very actively involved and motivated in learning activities. Therefore, the objectives of carrying out this research are: (1) To find out teacher strategies in increasing students' learning motivation in class VIII science subjects at SMP Negeri 2 Gunungsitoli. (2) To determine the supporting and inhibiting factors in increasing the learning motivation of students in class VIII science subjects at SMP Negeri 2 Gunungsitoli. The type of research used is qualitative research with a descriptive approach. The research location is at SMP Negeri 2 Gunungsitoli. The research population is class VIII students in the 2023/2024 academic year. Research instruments, namely: observation sheets, questionnaires and interviews. Research results: (1) Teacher strategies in increasing students' learning motivation are: making students actively involved in learning, choosing appropriate learning methods, creating a pleasant learning atmosphere, giving challenging assignments to students, giving awards, and appreciating success learners. (2) Supporting factors in increasing students' learning motivation are the enthusiasm for learning and curiosity of students in learning, the completeness of learning facilities and infrastructure, the attitude of teachers who have a work ethic as professional teachers. Meanwhile, the inhibiting factors in increasing students' learning motivation are when students lack focus in participating in learning activities, lack of facilities and infrastructure to support learning, and monotonous teaching strategies that are unpleasant. According to the research results, it can be concluded that if a teacher has developed a good and interesting teaching strategy, it will definitely be able to increase students' learning motivation.